Job-Related Competencies Desired By Those Who Hire International Development Consultants - Tim Kock; William Weeks (Journal of International Agricultural and Extension Education, 2015)
The purpose of this study was to describe industry (NGOs) perceptions of job-related competencies for entry-level international development consultants. An online questionnaire was used to collect data and 30 participants responded. Nine constructs were garnered from the research: conflict management and resolution, cultural diversity, management responsibility, personal and professional development, personal skills, program planning and evaluation, public relations, staff relations, and work habits. NGO management rated all nine constructs as somewhat important or important. When asked to rank the constructs in order of importance, participants ranked work habits as the most important followed by personal skills and management responsibility. Educational institutions are on the front-line in building nations, they educate students who build the future. Therefore, they need to be proactive and inquire what competencies will be needed to facilitate that outcome and prepare students for the global job market.
Keywords: international; competencies; NGOs; development